2023
DOI: 10.1002/advs.202206792
|View full text |Cite
|
Sign up to set email alerts
|

EHBP1L1 Drives Immune Evasion in Renal Cell Carcinoma through Binding and Stabilizing JAK1

Abstract: High lymphocyte infiltration and immunosuppression characterize the tumor microenvironment (TME) in renal cell carcinoma (RCC).There is an urgent need to elucidate how tumor cells escape the immune attack and to develop novel therapeutic targets to enhance the efficacy of immune checkpoint blockade (ICB) in RCC. Overactivated IFN-𝜸-induced JAK/STAT signaling involves in such TME, but the underlying mechanisms remain elusive. Here, EH domain-binding protein 1-like protein 1 (EHBP1L1) is identified as a crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…However, the efficacy of these therapies remains limited, with persistent immune suppression and resistance observed in the tumor microenvironment (TME). Therefore, it is imperative to identify new therapeutic targets to enhance the efficacy of immunotherapeutic agents for RCC 40 42 . Notably, targeting DHODH is a potential strategy for anti-ccRCC immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of these therapies remains limited, with persistent immune suppression and resistance observed in the tumor microenvironment (TME). Therefore, it is imperative to identify new therapeutic targets to enhance the efficacy of immunotherapeutic agents for RCC 40 42 . Notably, targeting DHODH is a potential strategy for anti-ccRCC immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CTSF expression was negatively correlated with the expression of several immunoinhibitors (including CTLA4, TIGIT, CD96, LAG3, CD274, BTLA, PDCD1LG2 and PDCD1), immunostimulators (including ICOS, CD80, TNFRSF9, IL2RA, CD28, LTA, TNFSF13B, MICB, TNFSF4, TNFSF14, KLRK1 and CD86), and MHC molecules (including TAP1 and TAP2) in ccRCC. Published work have shown that high lymphocyte infiltration and immunosuppression characterized the immune microenvironment in ccRCC and contributed to cancer development 28 , 29 . Infiltration of CD8 + T cells within the tumor microenvironment (TME) may be associated with a poor prognostic marker and may predict the response to immune checkpoint blockade (ICB) in ccRCC 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IFN-γ signalling can be effectively maintained within tumours through EH domain-binding protein 1-like protein 1 (EHBP1L1) shielding JAK1 from proteasomal degradation. This mechanism promoted PD-L1 expression in a mouse model of renal cell carcinoma (RCC) and EHBP1L1 inhibition resulted in increased CTL activity and improved response to ICBT [ 73 ].…”
Section: Negative-feedback Regulators Of Ifn-γ Signallingmentioning
confidence: 99%